A threshold panel model for exploring the nonlinear connection between entrepreneurship and economic growth - Mohammadi Khyareh, Mohsen (Journal of Economics and Business Letters, 2023)
The paper examines the relationship between entrepreneurship and economic growth, specifically focusing on the role of financial development as a factor that can influence this relationship. The authors employ the panel transition regression (PTR) model to analyze data from 96 countries spanning the years 2003 to 2020. The analysis reveals the presence of a threshold that determines the impact of entrepreneurship on economic growth. In the first regime, characterized by a lower level of financial development, the study finds no statistically significant influence of increased entrepreneurial activities on economic growth. This suggests that below a certain level of financial development, entrepreneurship alone may not contribute significantly to economic growth. However, in the second regime, which corresponds to a higher level of financial development, the study demonstrates a positive effect of increased entrepreneurial activity on economic growth. In this regime, an expansion of entrepreneurial endeavors leads to a beneficial impact on the overall economic growth of a country. These findings imply that there exists a minimum threshold of financial development required before it starts significantly contributing to economic growth. Once this threshold is surpassed, with the presence of adequate financial development, an increase in entrepreneurial activity can have a positive and substantial effect on a country's economic growth.